Avaliação e caracterização agroindustrial do sorgo sacarino visando a produção de etanol - Fernandes, Gislaine (2014)
Among the various renewable feedstocks available for ethanol fuel production, special emphasis has been given to sweet sorghum because the extracted juice of its stalk is composed of sucrose, glucose, fructose and can therefore be easily fermented to produce ethanol. In this paper we evaluate the behavior of the concentrations of sugars (sucrose, glucose, and fructose), nutrients (N, Ca, Mg, P) and starch in the juice from four sweet sorghum cultivars developed by Embrapa Maize and Sorghum (BRS 506, BRS 507, BRS 509, BRS 511) during time of maturation. The industrial use period was also determining the yield of cane and ethanol production using sweet sorghum juice in different planting dates. The cultivars showed different concentrations of sugars, industrial use period, and productivity between them as well as between the ages of plantings, showing influence of climatic conditions and the characteristics of each cultivar. All cultivars showed similar behavior with regard to nutrient content which were characterized by decreased concentration of nutrients throughout the analysis and increase in starch period. After fermenting both cultivars for 8 hours, it was found that cultivar BR 508 showed the best performance in terms of productivity (9.0 g/Lh) and yield (YP/ART = 90.5 %). Also, the feasibility of freezing the juice of sweet sorghum was verified and it was observed that after 30 days the levels of total sugars were reduced in their concentrations. Characterizations of sugar content were made in different parts of the stalk for the four cultivars and found that higher concentrations of total sugars are at the base of the stalk. Fermentations of the sorghum cultivars was carried out in order to evaluate the effectiveness of nutrient addition and stirring during fermentation process, which found that these two parameters did not add gains during fermentation. The fermented broths with different concentrations of sorghum sugar , in comparison with the juice of sugar, in order to evaluate the effect of different concentrations of total sugar (160, 180, 220, 260, and 300 g/L) yield the fermentation. It was found that with increasing sugar concentration, it did not increase the production of ethanol to concentrations of 160, 180, 220, and 260 g/L and the concentration was reduced to 300 g/L, showing inhibition on ethanol production when using sorghum broth with increased initial concentration of sugar and it has been found that yield and productivity in 8 hours of fermentation broth for the sorghum was from 0.8 to 4.8% and from 2 to 3.7% higher fermentations sugarcane juice under the same conditions. Reviews the use of enzyme a-amylase and amyloglucosidase the enzymatic hydrolysis of the juice in the juice of this sweet sorghum starch were made. It was noticed that the joint action of the addition of the two enzymes in the broth provided greater hydrolysis of starch present in the juice of sweet sorghum, an increase of 1.67 gallons of ethanol per ton of processed sweet sorghum .